A bottom–up regional potential assessment of bioenergy with carbon capture and storage in Germany - Mohammad Sadr; Danial Esmaeili Aliabadi; Matthias Jordan; Daniela Thrän (Environmental Research Letters, 2024)
Bioenergy with Carbon Capture and Storage (BECCS) is a bio-based Carbon Dioxide Removal Technology (CDR) undergoing detailed and comprehensive screening in many countries. The latest scientific reports emphasized that net-zero targets can not be achieved globally or nationally without deploying such technologies. Germany aims to achieve carbon neutrality by 2045, and negative emissions thereafter, which means a higher demand for CDRs. Despite BECCS being the building block of net-zero policies, its implementation on a national and regional scale presents serious challenges. Therefore, in this study, we analyze the role of BECCS in the German bioenergy system with a spatially detailed bottom–up optimization model that accounts for techno-economics and political aspects of BECCS (e.g. availability of biomass and investment costs). Our analysis demonstrates that BECCS can remove almost 61 Mt CO _2 in 2050; however, the outcomes demonstrate sensitivity toward CO _2 credit and CO _2 prices, which can raise the removal as high as 69 Mt CO _2 . Additionally, results suggest that removing enough CO _2 to achieve carbon neutrality in Germany by 2045 solely through BECCS seems extremely challenging; thus, a portfolio of negative emission technologies will be necessary to contribute. Our findings provide a better understanding of BECCS feasibility and its potential to assist us in achieving climate targets in Germany. Although we apply our model to Germany, the developed tool and insights are generic and can be applied to other countries.